Optimisation of storage and transportation conditions of cultured corneal endothelial cells for cell replacement therapy - Wahlig, Stephen (2021)
As the cornea is one of the most transplanted tissues in the body it has placed a burden on the provision of corneas from cadaveric donors. Corneal endothelial dysfunction is the leading indication for cornea transplant. Therefore, tissue engineering is emerging as an alternative approach to overcome the global shortage of transplant-grade corneas. The propagation and expansion of corneal endothelial cells has been widely reported. However, one obstacle to overcome is the transport and storage of corneal endothelial cells. In this study we investigated whether tissue engineered corneal endothelial cells can be preserved in hypothermic conditions. Human corneal endothelial cells (HCEnCs) were exposed to various temperatures (4 °C, 23 °C, and 37 °C) in both adherent and suspension storage models. Optimal storage media and storage duration was tested along with post-storage viability. Following storage and subsequent recovery at 37 °C, cell phenotype was assessed by immunofluorescence, gene and protein expression, and proliferative capacity analysis. Functionality was also assessed within a rabbit model of bullous keratopathy. Our data support our hypothesis that functional HCEnCs can be preserved in hypothermic conditions.